Chemical analysis of duck bone meal (Anatidae) from traditional food processing waste typical of Sidrap. Issue 1 (June 2021) - Qisti, N; Muslimin, I; Jumarni,; Najah, Z
Abstract: Sidrap Regency in South Sulawesi Province has special food, namely Palekko', which has duck as raw material. The number of palekko' stalls in Sidrap will raise concerns about the waste generated because there is no treatment at all. This waste will increasingly pollute the environment, if not managed properly. Therefore, the processing is carried out, namely the manufacture of duck bone meal. This duck bone meal was analyzed by chemical analysis to compare it with the SNI for the bone meal and other bone meal that had been tested. This research was conducted to know the potential use of duck bone meal to be maximized through chemical analysis. The chemical analysis carried out was the test of moisture, protein, fat, crude fiber, ash content, calcium, and phosphorus (P2O5). The results of the chemical analysis obtained were moisture, protein, fat, crude fiber, ash, calcium, and phosphorus content (P2O5) respectively, namely 2.01%, 33.33%, 12.38%, 2.78%, 41.66%, 2.53% and 6.24%. Then it compared with SNI a duck bone meal and others. The results obtained bone powder duck has the potential to be applied optimally produce products made from the bone meal of duck with doing some treatment to improve their quality.